PENGARUH PENGGEMBALAAN PRA NIKAH TERHADAP KESIAPAN EMOSIONAL DAN SPIRITUAL PASANGAN DALAM MEMASUKI PERNIKAHAN - Lumunder, Epafras Mario; Retor, Esther Avilita; Kreysen, Inriany F.; Bawihu, Sylvia Evangelin; Awalo, Meri Lusia; Wolter Weol (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2024)
This research explores the importance of premarital counseling and guidance programs in preparing couples to enter a harmonious and sustainable married life. The research was conducted using a literature review approach to analyze relevant literature, including books, scientific journal articles, and other relevant documents. The results show that premarital counseling programs play a crucial role in equipping couples with the necessary knowledge and skills, such as emotional readiness, effective communication skills, conflict resolution, and a deep understanding of the dynamics of marriage. The program also provides significant benefits in spiritual formation, which is important for enhancing the spiritual and emotional readiness of couples. Premarital shepherding helps couples understand the meaning and purpose of marriage according to spiritual values, improves communication and cooperation in family life, and strengthens commitment to marriage. This study emphasizes the need for adequate preparation through premarital counseling and guidance programs to reduce uncertainty and prepare couples for the challenges of married life.